Analysis of Posyandu Advisory Team Role in Preparing Six Minimum Service Standards Transformation - Nur Ahda Insan Febriani; Muhammad Ali Salman; Ridwan; Sri Wahyuni (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
The transformation of Posyandu based on the six Minimum Service Standards (SPM) is a strategic initiative to strengthen integrated community-based public services. However, its implementation in East Kalimantan Province remains at an early stage and faces challenges related to institutional readiness, human resource capacity, and cross-sectoral coordination. Therefore, this study aims to examine the role of the Posyandu Development Team in supporting the preparation for the implementation of SPM-based Posyandu. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and documentation involving nine purposively selected informants, consisting of three members of the Posyandu Development Team and six Posyandu cadres. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that the implementation of SPM-based Posyandu has not yet been fully supported by adequate institutional readiness and human resource capacity at the regional level. The Posyandu Development Team plays significant roles as a regulator, facilitator, and dynamizer through monitoring and evaluation, capacity building, cross-sectoral coordination, and efforts to enhance community participation. These findings contribute to a better understanding of the strategic role of the Posyandu Development Team in supporting the implementation of SPM-based Posyandu and provide practical recommendations for strengthening institutional capacity, improving cross-sectoral coordination, and enhancing community participation.